Minimally Invasive Ablation of a Toxic Thyroid Nodule by High-Intensity Focused Ultrasound - Esnault, O.; Rouxel, A.; Le Nestour, E.; Gheron, G.; Leenhardt, L. (American Journal of Neuroradiology, 2010)
SUMMARY: HIFU is used in the treatment of cancer (prostate, breast) and uterine fibroma but not yet in TNs. This case report describes the first successful ablation of a toxic TN with HIFU. TSH and radioiodine scan normalization were achieved without complications and maintained for 18 months. HIFU treatment is a minimally invasive technique that may be an effective safe alternative to radioiodine or surgery in patients with toxic TNs. AFTNautonomously functioning thyroid noduleENTears, nose, and throatFT3triiodothyronine, freeFT4thyroxine, freeHIFUhigh-intensity focused ultrasound123Iiodine 123TNthyroid noduleTSHthyroid-stimulating hormone, thyrotropin